VIDEO GAMES AS TECHNOLOGICAL RUINS OF A RECENT PAST - Metzitakos, Rossetos; Panagiotakopoulos, Dimitrios; Christodoulou, Marina (Design/Arts/Culture, 2020)
The aesthetic cultivation of societal recollection is inextricably linked to the approach and preservation of the objects and the mnemonics that accompany them. This perception in modern society includes in its dormitories the historical evolution and retrospect of technology whose origins are pervasive in the realization of social impulses. Nostalgia and memories are no longer moved only through traditional ruins that reflect the aesthetics and sense of social development. In this context, it is important to examine whether video games nowadays can classify the early technological structures into the cradle of modern ruins, the evolutionary course of social memory. This article scrutinizes the multi-dimensional aspects of video games, approaching them as historical and technological achievements and identifying their aesthetic value as objects of the recent past that further stimulate quests lurking in this pixelated romanticism.